Cultural integration: Experimental evidence of changes in immigrants' preferences - Lisa A. Cameron; Nisvan Erkal; Lata Gangadharan; Marina Zhang (Institute for the Study of Labor (IZA), 2012)
Cultural traits play a significant role in the determination of economic outcomes and institutions. This paper presents evidence from laboratory experiments on the cultural integration of individuals of Chinese ethnicity in Australia, focusing on social preferences, preferences for competition, and risk attitudes. We show that the greater the share of education an individual receives in the West, the more they behave like Western subjects and the less they behave according to the norms of their Eastern heritage. Increased exposure to Western education has a strong negative impact on altruism, trust, and trustworthiness. For risk and competitive preferences, our results are gender-specific. These results have important implications for policy making and institution building in multi-cultural societies.
urn:nbn:de:101:1-201208065494
Keywords: C91; J15; D64; D03; 330; cultural integration; cultural transmission; cultural diversity; cultural assimilation; acculturation; immigration; social preferences; preferences for competition; risk aversion; Soziale Integration; Chinesen; Multikulturelle Gesellschaft; Australien